2014
DOI: 10.4236/snl.2014.44012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CW CO<sub>2</sub> Laser Annealing on Indium Tin Oxide Thin Films Characteristics

Abstract: In this work ITO thin film annealing was carried out using a CW CO 2 laser beam for ITO thin film annealing over a 1 cm 2 area with a temperature higher than 250˚C to obtain ITO grains with excellent structural quality thin films. The obtained ITO films were characterized for crystallization, surface morphology, electrical and optical properties, which has theoretical significance and application value. ITO thin films are deposited on glass substrates by sputter coater system (RF) from a high density target (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…All three CVD samples exhibit characteristic features indicating an orthorhombic CsPbBr 3 phase [29], as also observed in the solution-processed reference sample. The signal at 35.4° can be assigned to the (400) planes of ITO [30]. It can be seen that the CVD samples processed with PbBr 2 temperatures of 340 °C and 360 °C in addition show multiple reflections which are not observed for the reference film.…”
Section: Resultsmentioning
confidence: 92%
“…All three CVD samples exhibit characteristic features indicating an orthorhombic CsPbBr 3 phase [29], as also observed in the solution-processed reference sample. The signal at 35.4° can be assigned to the (400) planes of ITO [30]. It can be seen that the CVD samples processed with PbBr 2 temperatures of 340 °C and 360 °C in addition show multiple reflections which are not observed for the reference film.…”
Section: Resultsmentioning
confidence: 92%
“…The seeds pattern could be shown in gure (2) which did not appear a peak without annealing. This case an amorphous structure was indicated [54,60]. The XRD patterns of ITO seeds at laser annealing temperature appear diffraction pattern with different major peaks of (211), ( 222), (400), (440), and (622), according with ICSD Card No.…”
Section: Resultsmentioning
confidence: 99%
“…To calculate the direct optical band gap (Eg) of the Cu 2 O nanoparticles estimated by Tauc plots (Fig. 7): α hv = A ( hv -Eg ) 1/2 , where ν is the photon frequency, h is Planck's constant, A being a constant, α is the absorption coe cient, [65,54]. The band gap energies decreased from 2.107 eV to 2.282 eV for Cu 2 O lm at temperature of 70 ℃, as showed in Table 3.…”
Section: Crystal Building Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al 25 discovered that CO 2 laser annealing can obviously increase the luminescent properties of Si-rich SiO films. Alsultany 26 reported that CO 2 laser annealing can effectively improve the crystallinity of ITO thin films, and then lead to increased electrical and optical properties. It is a remarkable fact that rapid heating and cooling can change the morphology and crystallinity of the thin film, and then further influence its luminescent properties.…”
mentioning
confidence: 99%